GEOINFORMATIONAL ANALYSIS OF THE CHERNIHIV POLESIE LOESS “ISLANDS” FOREST VEGETATION CHANGES - Yakovenko, Олександр (Biota. Human. Technology, 2023)
The purpose of the study. To find out the of the forest vegetation distribution of the loess Chernihiv Polesie ”islands” peculiarities and their area dynamics over the last 20 years. Methodology. Stationary geoinformation system QGIS 3.28 and interactive online resource “Global Forest Watch” (GFW) were used for remote monitoring of forest cover of Chernihiv Polesie loess ”islands”. Global Forest Watch (GFW) is an online platform that provides data and tools for monitoring forests. By harnessing cutting-edge technology, GFW allows anyone to access near real-time information about where and how forests are changing around the world. With the help of GFW, data on the area of the forest vegetation, the area of its loss and new plantations will be obtained. Scientific novelty. Remote studies of the forest vegetation changes dynamics in the territory of the Chernihiv Polesie forest “islands” of over the past 20 years have been carried out for the first time. Forested areas were recorded using QGIS 3.28 and Global Forest Watch. Observation of the forest cover changes dynamics for the period from 2000 to 2022 was carried out in the section of each of the loess ”islands” of the Chernihiv Polesie using space images and interactive online resource. Conclusions. The total of Chernihiv Polesie loess ”islands” forest cover was 7.9 % in 2000 and 8.9 % in 2022. The forest cover percentage values of loess ”islands” are follows: Mykhailo-Kotsiubynsk – 9.9 % & 12.13 %, Ripky-Chernihiv – 5.9 % & 6.85 %, Sedniv-Tupychiv – 5.8 % & 6.36 %, Berezna-Mena-Sosnytsia – 8.8 % & 9.7 %. respectively in 2000 and 2022. The forest vegetation area of each loess ”islands” increased, but the most on Mykhailo-Kotsiubynsk (by 2.2 %). For other ”islands”, this value is less than 1 %. Changes in the forest cover of the loess ”islands” are related to the dynamics of agricultural land areas, primarily the Berezna-Mena-Sosnytsia loess ”islands” territory. There was a slight increase in the loess ”islands” forests area due to the forest edges overgrowth and abandoned agricultural lands) during the studied period.